Understanding The Role of Attractiveness and Parasocial Interaction on Hedonics Consumption: Cognitive Assimilation as Mediating - Ratulangi, Agnes; Kuswati, Rini (Universitas Airlangga, 2024)
In the digital era, technological advancement has provided many benefits to the public in all aspects of life, including consumption. One example is the live-streaming phenomenon practised by beauty influencers. Live streaming is a feature that allows beauty influencers to communicate in real-time with their viewers. Gorgeous people are more liked and admired by others. Attractiveness and parasocial contact can affect hedonic consumption. The study distributed questionnaires to 205 social media users familiar with TF and who have used or previously used a product from brand X, particularly those who live in the Sukoharjo area. Based on the analysis using SEM (Structural Equation Modeling) and SMART PLS (Partial Least Squares), this study found that: 1. Attractiveness is positively associated with cognitive assimilation; 2. Attractiveness is not associated with hedonic consumption; 3. Cognitive assimilation positively influences hedonic consumption; 4. Parasocial interaction is positively connected to cognitive assimilation; 5. Parasocial interaction is positively associated with hedonic consumption; 6. Cognitive assimilation fully mediates the relationship between attractiveness and hedonic consumption, and similarly, cognitive assimilation also partially mediates the effect of parasocial interaction on hedonic consumption.